PERAN AGAMA TERHADAP ARSITEKTUR DESA KATOLIK PALASARI DAN DESA KRISTEN BLIMBINGSARI - Samuel Geovano; Franseno Pujianto (Riset Arsitektur (RISA), 2022)
Abstract - In Architecture and Order by (Pearson, 1993) , when explaining the relationship between architecture and culture, he used the term social space, which is a space formed by society through the habits, culture, and beliefs of a group of people. Social space can also be interpreted as a space created from the accumulation of group perceptions and beliefs in a space. Social space is formed from the relations of objects in space that generally facilitate and support the activities of a group of people. So, the social space that is formed should be able to accommodate the needs of activities and follow the identity of the people who inhabit it. In Jembrana Regency, there are two villages with unique cultures, Palasari Village and Blimbingsari Village. Palasari Village is a village with Balinese natives who embrace the Catholic religion, while Blimbingsari Village is a village with a homogeneous Balinese population who adheres to Christianity. Since the beginning, the two villages were designed with the values of religion and belief, Palasari Village was established with the "Dorf Model" which is a Catholic Village with a Balinese face, while Blimbingsari Village was designed to be a Christian village. This led to the formation of unique social, cultural and religious activities in these two villages. Over time, the two villages developed into tourist villages with the main attraction of pilgrimage tourism. This study aims to determine the role of religion in the architecture of Palasari Catholic Village and Blimbingsari Christian Village. The final result of this research is to reveal the role of religious culture on architecture in the two villages. This research is interesting to carry out because the studies that have been done on the two villages have not yet discussed the role of religion in the architecture of the two villages. Data collection in this study was carried out using observation, interviews, documentation, and a literature study method. Then the data collected is classified into morphological and topological data which will then be analyzed by (Pearson, 1993) theory of the influence of culture on architecture. The method used in this research is descriptive qualitative by describing the existing state of the two villages and revealing the relationship between belief and religious values with the architecture of the two villages. Based on this analysis, the two villages will be compared and conclusions are drawn based on the analysis result. It was concluded that the architecture of Palasari and Blimbingsari villages was influenced by the religion of each villager as a result of the application of conservative beliefs & religious values, religious activities & rituals, as well as ethnic, group & social order factors owned by residents of both villages. Keywords: religion, beliefs, Palasari Village, Blimbingsari Village